Oxidative IR spectroelectrochemistry of copper in methanol containing carbon monoxide - Brooksby, Paula A (Langmuir : the ACS journal of surfaces and colloids, 2014)
IR spectroelectrochemistry was used to examine the electro-oxidation behavior of carbon monoxide in methanol at a polycrystalline copper electrode. Under such neutral conditions copper electrodes are coated with ill-defined copper oxides and hydroxides and at the oxidative potentials can be expected to generate soluble copper species. The electrochemistry displayed complex behavior suggesting that methanol oxidation was one prominent reaction. However, the spectroscopy revealed that very little methanol oxidation had occurred and that carbon monoxide was not adsorbed to the copper electrode. Instead, the electro-oxidation generated an intense IR band at 2107 cm(-1) that was attributed to a soluble [Cu(I)CO](+) species